Chinese medicinal herbs for reducing endocrine therapy-induced side effects in patients with hormone receptor‐positive breast cancer: a systematic review and meta-analysis. (31st December 2023) - Chen, Shaoqing; Gao, Yifang; Liu, Haichao; Jing, Jin; Yang, Zhengyu; Zhu, Haoming; Chen, Bairui; Wang, Yu; Zhang, Ting; Wang, Shizhong; Lin, Jianping
Abstract: Context: Chinese medicinal herbs (CMH) have been considered a potentially efficacious approach for patients with breast cancer that experience adverse effects from endocrine treatment. Objective: To investigate the impact of CMH on endocrine therapy-induced side effects in patients with hormone receptor-positive (HR+) breast cancer. Methods: Ten databases (e.g., PubMed, Web of Science, Cochrane Library, China National Knowledge Information Database and other databases) were searched up to 20 May 2022. The search terms included Chinese herb, breast cancer, endocrine therapy, clinical trial and their mesh terms. The study selection and data extraction were performed by two independent reviewers. The risk of bias was evaluated using the Cochrane risk of bias method. Results: A total of 31 studies with 2288 patients were included. There were significant improvements in bone mineral density (BMD) [lumbar BMD ( MD 0.08, 95% CI 0.07 to 0.09, p < 0.00001) and femoral neck BMD ( MD 0.08, 95% CI 0.07 to 0.10, p < 0.00001)] and bone gal protein (BGP) ( MD 0.24, 95% CI 0.17 to 0.31, p < 0.00001), with a significant reduction in triglycerides (MD −0.53, 95% CI −1.00 to −0.07, p < 0.05) and no effect on estradiol levels (MD 0.90, 95% CI −0.31 to 2.12, p = 0.15). Conclusions: CMH combined with complementary therapy can moderately reduce endocrine therapy-induced side effects, including bone loss and dyslipidemia in patients with HR + breast cancer, revealing the potential role of CMH in treating (HR+) breast cancer. More high-quality RCTs are warranted to further validate the effectiveness and safety of CMH.